Introduction of positions of cyber protection officers in public authorities as an improvement of state cyber security - L.A. (Економіка, управління та адміністрування)
The world of IT is quite large and diverse. It is actively developing, subordinating almost everything around. The trend towards the development of the field of cyber security has also affected the environment, regularly creating new professions related to IT technologies. It is absolutely certain that the field will continue to develop actively in the coming decades, providing good opportunities for IT specialists in various fields. The IT sphere does not stand still at all and completely new professions await us in the nearest future. Today, the field of cyber security in Ukraine is perhaps the most in-demand in the near and distant future. The IT industry already needs a large number of web developers, programmers, game developers and analysts in the field of computing, information security analysts. The conducted analysis proved that the intensive growth of information technologies in the future will create both demand and supply, including for cyber security specialists. The introduction of the positions of cyber protection officers in public authorities will ensure further resistance to those cyber threats that threaten the national security of Ukraine, exchange of experience, approaches, joint cyber training, as well as minimization of opportunities for cyber attacks. In addition, the introduction of cyber protection officer positions in state authorities and critical infrastructure facilities will be an effective «catalyst» in the further creation of tools for financial incentives for employees who perform IT system administration tasks, will make it possible to strengthen the responsibility of officials for non-compliance with cyber protection requirements , will make it possible to implement requirements in «contracted» organizations that work with state authorities, and to eliminate critical vulnerabilities in state authorities and critical infrastructure facilities.